Return to work for patients with diffuse large B-cell lymphoma and transformed indolent lymphoma undergoing autologous stem cell transplantation - Arboe, Bente (Clin Epidemiol, 2017)
BACKGROUND: Autologous stem cell transplantation (ASCT) is the standard treatment for patients with relapsed diffuse large B-cell lymphoma (DLBCL) or transformed indolent lymphoma (TIL). The treatment is mainly considered for younger patients still available for the work market. In this study, social outcomes after ASCT in terms of return to work (RTW) are described. PATIENTS AND METHODS: Information from national administrative registers was combined with clinical information on patients, who received ASCT for relapse of DLBCL or TIL between 2000 and 2012. A total of 164 patients were followed until RTW, disability or old-age pension, death, or December 31, 2015, whichever came first. A total of 205 patients were followed with disability pension as the event of interest. Cox models were used to determine cause-specific hazards. RESULTS: During follow-up, 82 (50%) patients returned to work. The rate of returning to work in the first year following ASCT was decreased for patients being on sick leave at the time of relapse (hazard ratio [HR] 0.3 [0.2;0.5]) and increased for patients aged ≥55 years (HR 1.9 [1.1;3.3]). In all, 56 (27%) patients were granted disability pension. Being on sick leave at the time of relapse was positively associated with receiving a disability pension in the first 2 years after ASCT (HR 3.7 [1.8;7.7]). CONCLUSION: Patients on sick leave at the time of relapse have a poorer prognosis regarding RTW and have a higher rate of disability pension. Furthermore, patients >55 are more likely to RTW compared to younger patients. These results indicate an unmet need for focused social rehabilitation.